Methods of albumin estimation in clinical biochemistry: Past, present, and future - Kumar, Deepak; Banerjee, Dibyajyoti (Clinica chimica acta, 2017)
Estimation of serum and urinary albumin is routinely performed in clinical biochemistry laboratories. In the past, precipitation-based methods were popular for estimation of human serum albumin (HSA). Currently, dye-binding or immunochemical methods are widely practiced. Each of these methods has its limitations. Research endeavors to overcome such limitations are on-going. The current trends in methodological aspects of albumin estimation guiding the field have not been reviewed. Therefore, it is the need of the hour to review several aspects of albumin estimation. The present review focuses on the modern trends of research from a conceptual point of view and gives an overview of recent developments to offer the readers a comprehensive understanding of the subject. Albumin estimation in clinical laboratory•Precipitation methods: obsolete•Dye binding methods: non-specific (interacts with globulins or anionic agents)•Immunochemical methods: less – sensitive (fails to detect un-reactive fragment)•HPLC based methods: reference method; but not currently possible at POC•Various novel research findings are there that may revolutionize the field.